2018
DOI: 10.3892/ijmm.2018.3390
|View full text |Cite
|
Sign up to set email alerts
|

NOX4/ROS mediate ethanol‑induced apoptosis via MAPK signal pathway in L‑02 cells

Abstract: The aim of the present study was to assess the molecular mechanism of ethanol‑induced oxidative stress‑mediated apoptosis in L‑02 liver cells in order to elucidate novel pathways associated with alcoholic liver disease. L‑02 cells were treated with 400 mM ethanol with or without inhibitors. The cell viability was measured by an MTT assay. Cell apoptosis was assessed by flow cytometry and a single‑stranded DNA (ssDNA) assay. Intracellular reactive oxygen species (ROS) production of L‑02 cells was determined usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…Although the method of displaying concentration is different, 100 ~ 200 mM EtOH induces ~30% cell death. In line with our study, cell death is induced by ~50% in human normal liver cells L-02 treated with 400 mM EtOH for 24 h [ 41 ]. The 2% EtOH used in this study is a very high concentration with 50% cytotoxicity.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Although the method of displaying concentration is different, 100 ~ 200 mM EtOH induces ~30% cell death. In line with our study, cell death is induced by ~50% in human normal liver cells L-02 treated with 400 mM EtOH for 24 h [ 41 ]. The 2% EtOH used in this study is a very high concentration with 50% cytotoxicity.…”
Section: Discussionsupporting
confidence: 85%
“…In general, 100 mM is used to induce cell injury. However, even in reports, 100 mM EtOH induces cell death approximately 25% of the time [ 40 , 41 ]. These results are similar to our results.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that alcohol can cause alcoholic liver damage by activating oxidative stress, inhibiting liver fat-acid metabolism, and increasing liver lipid synthesis (Li et al, 2017;Li et al, 2018;Yang C. F. et al, 2018). Studies have also revealed that alcohol reduces hepatic glycogen synthesis and increases gluconeogenesis by regulating the liver insulin signaling pathway (Pang et al, 2009;Magdaleno et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, NOX4 participation in the stress‐induced human islet cell death process has been demonstrated using a NOX4 inhibitor . Also, it has been reported that elevated NOX4 expression by ethanol induced ROS generation, which causes cell death in hepatocytes . It has also been shown that NOX4 also participated in the death of TGF‐β–induced hepatocytes .…”
Section: Discussionmentioning
confidence: 97%